(untitled) (Scientific journal of the Fergana State University, 2026)
This article analyzes the necessity of implementing innovative methods in entrepreneurial activity, the impact of innovative methods on economic efficiency, competitiveness, and the sustainable development of society. The role and significance of innovative approaches in entrepreneurial activity in the development of society are also scientifically substantiated.